Porous chitosan/partially reduced graphene oxide/diatomite composite as an efficient adsorbent for quantitative colorimetric detection of pesticides in a complex matrix. Issue 14 (21st June 2021) - Ma, Guicen; Cao, Jianrong; Hu, Gaohua; Zhu, Li; Chen, Hongping; Zhang, Xiangchun; Liu, Jiahao; Ji, Jingjing; Liu, Xin; Lu, Chengyin
Abstract : An efficient adsorbent (CS/prGO/DM composites) was successfully synthesized. It exhibited high removal ability towards tea interferents. A colorimetric sensing platform based on Au NPs for quantitative detection of pesticides in tea was developed.  Abstract : On-site, instrument free quantitative analysis of pesticides is of significant importance for food safety control. However, it is still a great challenge for pesticide detection in food via the current visual detection methods due to the presence of interferents in a complex matrix. In this study, a complex tea matrix had a strong effect on a gold nanoparticles (Au NPs) based colorimetric sensor for the detection of pesticides. Here, a porous chitosan/partially reduced graphene oxide/diatomite (CS/prGO/DM) composite was successfully synthesized via a facile hydrothermal treatment. It could act as an efficient adsorbent for removing different types of tea interferents. A colorimetric sensing platform for the quantitative detection of pesticides in a complex matrix was successfully established. The color changes of the aggregation of Au NPs induced by pesticides were captured using the camera of a smartphone and the images were processed with average RGB (red, green, and blue) values obtained using self-developed software. The G/R values and A700/525 values obtained from UV-vis spectra could be used for quantitative analysis of pesticides. The limits of detection of phosalone and thiram in tea were 90 nM and 13.8 nM, respectively. It is expected that graphene-based materials are attractive for wide application of on-site colorimetric quantitative detection in a variety of fields like environmental protection, food safety and bioanalysis.